Association between the type of major duodenal papilla and difficult biliary cannulation in a private tertiary center - Gutierrez-De Aranguren, Constantino (2021)
Introduction: Difficult cannulation in cases of endoscopic retrograde cholangiopancreatography (ERCP) could be associated with several factors, including: type of major papilla, however, there are limited data regarding this possible association. Objectives: To determine the association between the type of papilla and difficult biliary cannulation. Materials and methods: A retrospective cross-sectional analytical study was conducted in patients over 18 years old who underwent ERCP on papilla naive, from July 2019 to April 2021, in a private institution. Unsuccessful cannulations were excluded. The papilla was classified based on Haraldsson classification. The crude association and adjusted for possible confounders between the type of papilla and difficult cannulation was evaluated. Relative risks (RR) and 95% confidence intervals were calculated. Results: 188 patients were included. The mean age was 55 years, 66% female. The most frequent indication was choledocholithiasis with 88.5%. The most frequent type of major duodenal papilla was type 1 (32%), followed by type 3 (27%), type 2 (25%) and type 4 (16%). Type 2, 3, 4 papillae showed a significant relationship with difficult cannulation compared to type 1 (p<0.001, p<0.001 and p=0.008 respectively). The indication other than choledocholithiasis also showed a significant relationship with difficult cannulation (p<0.001). In the adjusted analysis, the RR for difficult cannulation compared to type 1 papilla was: 2.51 (95% CI 1.23-5.94) for type 2 papilla, 3.72 (95% CI 1.79-7.71) for papilla type 3 and 3.41 (95% CI 1.54-7.71) for type 4. The indication other than choledocholithiasis was also associated with a higher risk of difficult cannulation with a RR of 2.36 (95% CI 1.57-3.56). The fistulotomy type precut was used more frequently in the type 3 papilla (46%), while the use of cannula was more frequent in the type 4 papilla (29.6%). Conclusions: Papilla types 2, 3 and 4 are associated with a higher risk of difficult cannulation. This should be considered when performing ERCP in order to reduce the risk of complications.